1988
DOI: 10.1507/endocrine1927.64.11_1124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shakuyaku-Kanzo-To, Shakuyaku, Kanzo, Paeoniflorin, Glycyrrhetinic Acid and Glycyrrhizin on Ovarian Function in Rats

Abstract: It is known that amenorrhea, oligomenorrhea, irregular menstrual cycles, luteal insufficiency and infertility are frequently associated with hyperandrogenism. It has been reported in previous studies that the traditional herbal medicine, Shakuyaku-Kanzo-To(SKT) can lower high serum testosterone levels in oligomenorrheic or amenorrheic women, and that some of these sterile women conceive. SKT contains Shakuyaku (S) and Kanzo (K) in equal amounts. The main component of S and K is paeoniflorin and glycyrrhizin, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This testosterone-lowering effect was also experimentally confirmed in ovarian culture of licorice-treated female rats [37,38]. Therefore, it was proposed that licorice could cause the deficiency of serum testosterone, leading to sexual dysfunction or decline of libido in men [1,2].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This testosterone-lowering effect was also experimentally confirmed in ovarian culture of licorice-treated female rats [37,38]. Therefore, it was proposed that licorice could cause the deficiency of serum testosterone, leading to sexual dysfunction or decline of libido in men [1,2].…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, however, Sakamoto & Wakabayashi [30] showed that oral administration of a Kanzo preparation, glycyrrhizin or glycyrrhetinic acid decreased in vitro testosterone production in Leydig cells of rats stimulated by luteinizing hormone. The testosterone-reducing effect of glycyrrhizin and glycyrrhetinic acid was observed in female rats [37,38], but not in males [the present study], and there is controversy over the influence of licorice in men [1,2,16,25]. It is hypothesized that, in spite of partial suppression of the basal production of testosterone following the inhibition of steroid-metabolizing enzymes by licorice, production of testosterone stimulated by luteinizing hormone is significantly blocked in the testes, or in the ovaries in the proestrous cycle [3,6,18,30,37,38,44].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[8][9][10][11] Animal studies further demonstrated that PGD and its major constituents possess a capacity of modulating synthesis and release of several sexual and reproductive hormones, including PRL. [21][22][23][24][25] The observations have led to a hypothesis that PGD may possess comparable efficacy and a safer profile compared with conventional dopamine agonists in the treatment of hyperprolactinemia associated with antipsychotic therapy. To test this hypothesis, we conducted a comparative study of PGD versus BMT as additional therapy in schizophrenic females with risperidone-induced hyperprolactinemia using a randomized crossover design.…”
mentioning
confidence: 99%
“…It has been in the widespread treatment of gynecological disorders such as dysmenorrheal , PCOS , endometriosis, and adenomyosis for thousands of years in Asia. Since 1980s, Japanese researchers have conducted the experimental studies on the therapeutic effects of SGD on PCOS and shown that the formula was effective for achieving pregnancy in patients with PCOS and improving their hyperandrogenism symptoms . Modern studies have showed that the main bioactive compounds of SGD including monoterpene glucosides, flavonoids, and triterpenoid saponins contribute a lot to the pharmacodynamic material basis in therapy of PCOS .…”
Section: Introductionmentioning
confidence: 99%